Effectiveness of e-module based on Google Sites in plant diversity courses on creative thinking skills of biology students - Veren Lativa; Murni Sapta Sari; Frida Kunti Setiowati (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2024)
One way to empower creative skills in the Plant Diversity course is through the use of e-modules. The low creative thinking skills of students can be improved by developing teaching materials in the form of e-modules. Electronic modules are electronic teaching materials that are arranged systematically and require innovation and utilization of technology in the field of education. The e-module developed is based on Google Sites which can be accessed by students online. This study aims to see the effectiveness of using Google Sites-based e-modules in Plant diversity courses on the creative thinking skills of Biology students. This research is a development research with ADDIE development model. The data analysis technique uses quantitative descriptive data analysis. The subjects in the research were biology students in 2021 with a total of 32 people. The results of the effectiveness of the Google Sites-based e-module were analyzed using the N-Gain calculation with a score obtained of 0.7338 with a high effectiveness category. So that the Google Sites-based e-module developed is effective in improving creative thinking skills. It is hoped that this e-module can help students in the learning process and improve creative thinking competencies in students.Abstrak. Salah satu cara memberdayakan keterampilan kreatif dalam mata kuliah Keanekaragaman Tumbuhan adalah melalui pemanfaatan e-modul. Rendahnya keterampilan berpikir kreatif mahasiswa dapat ditingkatkan dengan mengembangkan bahan ajar berupa e-modul. Elektronik modul merupakan bahan ajar elektronik yang disusun secara sistematis dan menuntut inovasi dan pemanfaatan teknologi di bidang pendidikan. E-modul yang dikembangkan berbasis Google Sites yang dapat diakases oleh mahasiswa secara online. Penelitian ini bertujuan untuk melihat efektifitas penggunaan e-modul berbasis Google Sites pada mata kuliah keanekaragaman Tumbuhan terhadap keterampilan berpikir kreatif mahasiswa Biologi. Penelitian ini merupakan penelitian pengembangan dengan model pengembangan ADDIE. Teknik nalisis data menggunakan analisis data deskriptif kuantitatif. Subjek dalam penleitian mahasiswa biologi tahun 2021 dengan jumlah 32 orang. Hasil efektifitas e-modul berbasis Google Sites dianalisis dengan menggunakan perhitungan N-Gain dengan skor yang diperoleh sebesar 0,7338 dengan kategori efektifitas tinggi. Sehinggaa e-modul berbasis Google Sites yang dikembangkan efektif dalam meningktakan keterampilan berpikir kreatif. Diharapkan dengan adanya e-modul ini bisa membantu mahasiswa dalam proses pembelajaran dan meningkatkan kompetensi berpikir kreatif pada mahasiswa.